Evaluation of genotypic diversity of Streptococcus mutans using distinct arbitrary primers - Cínthia Pereira Machado Tabchoury; Maria Clara K. Sousa; Rodrigo Alex Arthur; Renata Oliveira Mattos-Graner; Altair Antoninha Del Bel Cury; Jaime Aparecido Cury (University of São Paulo, 2008)
Streptococcus mutans has been considered one of the main etiological agents of dental caries and the genotypic diversity rather than its salivary counts may be considered as a virulence factor of this bacterium. For genotyping with polymerase chain reaction (PCR) with arbitrary primers, several primers have been used in order to improve complexity and specificity of amplicon patterns. Thus, the aim of this study was to evaluate the degree of agreement of genotypic identification among AP-PCR reactions performed with 5 distinct arbitrary primers of S. mutans isolated from saliva. Stimulated saliva was collected from 11 adult volunteers for isolation of S. mutans, and a total of 88 isolates were genotyped with arbitrary primers OPA 02, 03, 05, 13 and 18. Fourteen distinct genotypes were identified in the saliva samples. Most volunteers (9 out of 11) presented only one genotype. The results of the present study suggest that primers OPA 02, 03, 05 and 13 were suitable for genotypic identification of S. mutans isolates of saliva from adult volunteers.